Supramolecular Assemblies: Exciton Dynamics and Effects of Structural Order in Morphology‐Controlled J‐Aggregate Assemblies (Adv. Funct. Mater. 21/2019). (21st May 2019) - Anantharaman, Surendra B.; Stöferle, Thilo; Nüesch, Frank A.; Mahrt, Rainer F.; Heier, Jakob
Abstract : In article number1806997, Rainer F. Mahrt, Jakob Heier, and co‐workers report the exciton dynamics of different J‐aggregate assemblies grown on a substrate that increases domain size and crystalline order compared to J‐aggregates adsorbed from solution. The radiative decay of excitons is significantly enhanced and can be correlated to the increased order. Exciton‐charge quenching is identified as an additional non‐radiative decay channel impeding exciton migration in J‐aggregate thin films.